Internship at bilingualism for peace program from University of Cordoba at la ribera school. (2020)
Internships are professional practicums carried out by university students, generally during the last years of the degree, to put into practice the knowledge and faculties learned in a real working context. Besides, the intern has the purpose of improving or solving a problem found in that context. My internship was developed in a program offered by the University of Cordoba, called Bilingualism for peace at la Ribera high school in Monteria, Cordoba. I was working with pre-intermediate level students. In this level the vast majority of students had difficulties in expressing themselves verbally (speaking skill). To improve this, I decided to base my teaching method on various pedagogies (PBL, culturally responsive pedagogy, and intrinsic motivation). Throughout this process, I grew as a teacher, and as a person; I realized how difficult and challenging is this job but, it is also rewarding to see students’ progress and how they got more interested in a subject.